Análise morfométrica das sub-bacias de 3ª ordem da bacia hidrográfica do Rio do Peixe, Minas Gerais - Isabela Belmira Santos Giarola; Cinthia Maria Amaral; Daiane Evangelista de Oliveira (Confins)
Morphometry is fundamental for understanding the environmental dynamics of a given area. The morphometric and morphological analysis in watersheds is aimed at understanding the modeling of relief and local and regional fluvial dynamics and, through the application of morphometric parameters, the behavior of these units can be quantitatively evaluated. The watershed of the Peixe river, located in the southeast of the state of Minas Gerais, Brazil, presents in its territory morphometric specificities when compared to surrounding areas and, in order to investigate these morphometric characteristics, this work had the objective of understanding and explaining, methodologically based In geomorphological and morphometric interpretations, the heterogeneity of the modeling of the third-order sub-basins that make up the southern portion of the Peixe river basin. For the spatialization of the results of the calculations of the morphometric parameters, thematic maps were generated that aided in the comparative interpretations. After analyzing the results it was possible to conclude that the singularities found to the north and west of the southern portion of the catchment area of ​​the Peixe River may be related to the lithological and altimetric variation.